2005
DOI: 10.1177/0146167204271563
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between Religion and Spirituality and Psychological Adjustment: The Mediating Role of Optimism and Social Support

Abstract: Although optimism, social support, religiousness, and spirituality are important predictors of adjustment, rarely have studies examined these variables simultaneously. This study investigated whether optimism and social support mediated the relationship between religiousness and adjustment (distress and life satisfaction) and between spirituality and adjustment. Findings indicate that the relationship between intrinsic religiousness and life satisfaction and between prayer fulfillment and life satisfaction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
163
0
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(187 citation statements)
references
References 43 publications
16
163
0
8
Order By: Relevance
“…Indeed, several pioneering studies have shown that social supports and other positive psychological variables, such as altruism and optimism, may mediate the association between religious involvement and health (Krause, 2005;Salsman, Brown, Brechting & Carlson, 2005;Steffen & Masters, 2005). However, such findings have been limited by lack of objective measures of physical health, as well as by crosssectional and retrospective research designs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several pioneering studies have shown that social supports and other positive psychological variables, such as altruism and optimism, may mediate the association between religious involvement and health (Krause, 2005;Salsman, Brown, Brechting & Carlson, 2005;Steffen & Masters, 2005). However, such findings have been limited by lack of objective measures of physical health, as well as by crosssectional and retrospective research designs.…”
Section: Introductionmentioning
confidence: 99%
“…As will be discussed later, these may be some of the mediating factors between religiousness and well-being. 50 In a high-quality research study involving a US national sample of 1126 non-institutionalized older people, the feeling of closeness with God was related to optimism after controlling for sociodemographic variables. This optimism, in turn, had a strong influence on their self-rated health status.…”
mentioning
confidence: 99%
“…Despite the full mediating effects of optimism constructs, spirituality presented significant indirect effects on depression through optimism and pessimism, whereas Salsman et al 17) 's study reported a non-significant indirect effect of spirituality on depression through optimism. The significant results may be because of using a clinical sample that may be more psychologically distressful sample than college students used in the Salsman et al's 17) study.…”
Section: Discussionmentioning
confidence: 73%
“…The significant results may be because of using a clinical sample that may be more psychologically distressful sample than college students used in the Salsman et al's 17) study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation